(untitled) (Proceedings of the International Conference on Public Health, 2022)
Hyperthyroidism is the excessive production of thyroid hormone causing palpitation, hypertension, weight loss, heat intolerance, tremor, anxiety, etc. Hyperthyroidism in elderly patients does not display typical features, making diagnosis difficult. Hyperthyroid myopathy in elders is often mistaken for normal aging. It involves mostly proximal muscles for unclear reasons. This case reports hyperthyroidism in an elderly patient. A 70-year-old female was presented with chest discomfort intermittently for over 10 years and exacerbated for 10 days. This discomfort was described as chest tightness and palpitation. She also experienced shortness of breath. On physical examination, an enlarged thyroid was palpated. Thyroid ultrasound revealed diffuse thyroid nodules. Thyroid function tests showed increased free and total triiodothyronine, free thyroxine, thyrotropin receptor antibodies, as well as a decreased thyroid-stimulating hormone. Her clinical findings and lab tests were consistent with Graves’ disease, a condition of hyperthyroidism. Her condition was well managed with an antithyroid drug and beta-blocker. Hyperthyroidism in elderly patients may present only with cardiovascular disorders such as atrial fibrillation. In this case, the patient only displayed chest tightness and palpitation. Diagnosing hyperthyroidism in elders requires vigilance and we should not dismiss any diagnostic hint. Through literature review, a potential link between hyperthyroid myopathy and mitochondrial pathology is observed, which can be further investigated using mitochondrial histochemistry and beta-blockade experiment. This study hopes to promote awareness of thyroid diseases in the elderly population and address the issue of myopathy in elders due to thyroid diseases.